Validity and reproducibility of chest expansion measurement by a device using an ultrasonic sensor - Chanavirut, Raoyrin; Luangaram, Saowanee; Riyamongkol, Panomkhawn (Journal of Associated Medical Sciences, 2023)
Background: Chest expansion is a type of physical examination used by physicians and physical therapists to diagnose various pulmonary diseases. Despite the fact that it can be performed using various equipment. However, it has some limitations while operating in the clinic. Therefore, a prototype device was developed. Objectives: The study was carried out to assess the validity and reproducibility of a chest expansion measurement device using an ultrasonic sensor. Furthermore, the opinion to the device was gathered by the questionnaire. Materials and methods: The study included 110 healthy subjects ranging in age from 20-60 years old. Two examiners measured upper, middle, and lower chest expansion independently and at random, and the measurements were repeated one day later. The Pearson correlation coefficients and Bland-Altman plotting were then used to assess validity and reproducibility. In addition, a questionnaire yielded suggestions from 10 experienced physical therapists. Results: The results showed that the validity, as measured using Pearson’s correlation coefficient, had a moderate association in the lower part (r=0.69, p<0.001), whereas the other levels had the lowest and lowest association. There was also a strong correlation between intra-observer reproducibility (upper and middle: r=0.81, lower: r=0.84, all p<0.001). According to the questionnaire responses, some aspects of the device’s appearance should be improved. Conclusion: The device’s validity appears to be very low to moderate depending on the expansion levels measured. Additionally, the reproducibility is considerably high, while some details of the device need to be improved to maximize its efficiency.